Shatranj ke Khilari – A Semiological Analysis with Roland Barthes Approach - Anketa, Kumar; Sunil , Kumar (International Journal of Psychosocial Rehabilitation, 2019)
This paper focuses on Media study which is an emerging field within visual studies. To understand the phenomenon of semiotics we have adopted Ronald Barthes approach who was born in November 19151(1), according to whom an image is a medium of communication having a signifier and signified. This approach provides a new essence to the selected movie taken as case to explain shots communicating verbally and nonverbally. The paper addresses the novel approach of semiotics allowing media to examine the signs in a given image. This analysis explains that how connotative meanings of visuals are derived even by nonverbal communication. This approach contains fresh semiotics with costume and colors as sign indicators. This paper is an attempt to understand that how semiology can be applied to visuals in media studies. The qualitative study conferring Roland Barthes perspective analyses within the messages or images are purposefully shown to the viewer. The paper will analyze Shatranj ke Khiladi (Chess players), a Hindi film by renowned director Satyajit Ray as case study of a narrative around 1856 in Awadh - a princely state in India.